Pola Komunikasi Masyarakat Lembak dan Jawa Desa Durian Mas Rejang Lebong - Exsan, Exsan Adde; Deti Andeti (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2023)
Durian Mas Village is an area located in the area of ​​the Central Kepungut Tribe Marga, Padang Ulak Tanding District (formerly the main sub-district), where in 1992 it was expanded to become the Padang City District. Patterns of intercultural communication in Durian Mas Village, Rejang Lebong Regency, are the subject of this research. There are two tribes in Durian Mas village, namely the Lembak tribe and the Javanese tribe. The purpose of this research is to study how people from different cultural backgrounds communicate in the village of Durian Mas. This research is a qualitative descriptive field research with the aim of accurately establishing systematic qualitative descriptive facts and the characteristics of certain regional groups. This research data collection methods include interviews, observation, and documentation. The result of the research is that from the results of this study it was found that people who used to use oral communication from the local language, the language was interpreted and used in a group environment and was considered a common language. While the nonverbal communication used in the communication activities of the Lembak and Javanese people in Durian Mas Village are body language, appearance and clothing. Nonverbal language is used to support the meaning of information in society using nonverbal language to strengthen and complement language so that it can communicate effectively. Supporting factors in this intercultural communication process are the ability to communicate, mutual trust, friendly and polite attitude, interest in communicating, and adaptability.